MECANISMOS SOCIAIS NA REGULAÇÃO DE OPERAÇÕES FINANCEIRAS EM COOPERATIVAS DE CRÉDITO - Alair Ferreira de Freitas (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
Taking as object of study the rural credit unions Ecosol system in Minas Gerais, this paper sought to examine, through a qualitative study, how social mechanisms interfere in the operation of financial services these organizations. Trust, reputation and social networks deployed to monitor and control credit unions, take the form of governance structures, conceptions of control and standards for transactions that allow actors to construct patterns of financial relationship. Proximity is a characteristic significant relationship dynamics that permeates these organizations and their interactions in markets.